(untitled) (American Scholar: Journal of Interdisciplinary Research and Knowledge, 2026)
This article examines the methodology for applying the case study method as an effective tool for fostering professional-communicative competence among technical students studying the German language. Based on a pedagogical experiment, the author explicates the structure of a specialized case study designed to simulate a real-world production task. The research results demonstrate that integrating a professional context into the language training process not only enhances student motivation but also facilitates the simultaneous development of "soft skills" (such as teamwork and analytical thinking) and specialized technical terminology.